Community flood risk assessment in selected areas in Muntinlupa City - Masanga, L.P.; Caballero, R.V. (International Journal of Scientific Research and Management (IJSRM), 2024)
The study's objective is to hopefully create a profound awareness in the city government of Muntinlupa of the plight the community is experiencing.  A quantitative research design was utilized in this study. Flood risk perception: The probability of whether a retention pond, increasing the diameter of the existing reinforced concrete pipes, and or increasing the road elevation can be a permanent or a quick-fix solution is still unknown until the local government can conduct a comprehensive technical and environmental assessment of the different vulnerability factors in the community. No significant differences were found between age, years of residency, and flood risk perception. Flood risk preparedness: No significant differences existed between age, years of residency, and flood risk preparedness. Substantial differences were found between gender and flood preparedness, and they favor the male gender. Flood risk awareness: No significant differences existed between age, years of residency, and flood risk awareness. There were substantial differences between gender and flood awareness, and they favored the male gender. The study's recommendations encourage the local government of Muntinlupa to conduct a comprehensive administrative, technical, and environmental assessment of the different vulnerability factors facing the selected areas in the community.